FOOD HABITS AND LENGHT-WEIGHT RELATIONSHIP OF LUKAS FISH (Labiobarbus leptocheilus Valenciennes) IN GAJAH MUNGKUR RESERVOIR CENTRAL JAVA - Ridho, Moh Rasyid; Patrino, Enggar; Utomo, Agus Djoko; Aida, Siti Nurul (BIOVALENTIA: Biological Research Journal, 2017)
The Research about the food habits and length-weight relationship of Labiobarbus leptocheilus Valenciennes was conducted from May to September 2010. The aims of this research were to find out the food habits and to analyze the growth pattern of Labiobarbus leptocheilus Valenciennes. The sampling of fishes was conducted on May 2010 in the Gajah Mungkur Reservoir, Central Java. The sampling of fishes was conducted by using survey on the landing place of fishes (TPI Mina Tirta). The methods of analysis of food habits by using the Index of preponderance. The results of this research obtained were 19 samples of Labiobarbus leptocheilus Valenciennes, the length between 15-20 cm, with the weight between 40-90 grams. Labiobarbus leptocheilus Valenciennes had the negative allometric growth pattern (b <3). The laboratory analysis of food habits showed that the food habits of Labiobarbus leptocheilus Valenciennes were detritus with Index of Preponderance (IP) 82.95% and plankton with IP 17.05%.Keywords: food, habits, length-weight, relationship, Labiobarbus leptocheilus